2022
DOI: 10.18388/abp.2020_6408
|View full text |Cite
|
Sign up to set email alerts
|

Influence of age, gender characteristics, chronotype on the expression of core clock genes Per1, Clock, Bmal1 and Cry1 in buccal epithelium

Abstract: The purpose of the study is to determine the expression of the core clock genes in buccal epithelial cells of healthy people with different chronotypes. Materials and methods. Fourteen healthy volunteers with a healthy periodontium and oral mucosa (7 women and 7 men) were selected for participation in the trial. The buccal epithelium sampling was performed at 07:00 am and 07:00 pm in one day by cytological brush. The surveyed patients were examined chronotypically using the Horn-Ostberg test. The determination… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
1
0
1
Order By: Relevance
“…Previously, when studying the expression of circadian genes over time between groups of chronotypes, regardless of gender and age of participants, it was demonstrated that the extreme evening chronotypes have a delayed phase of fluctuations in the per3 and nr1d2 circadian clock genes compared to the extreme morning types. 19 , 20 …”
Section: Discussionmentioning
confidence: 99%
“…Previously, when studying the expression of circadian genes over time between groups of chronotypes, regardless of gender and age of participants, it was demonstrated that the extreme evening chronotypes have a delayed phase of fluctuations in the per3 and nr1d2 circadian clock genes compared to the extreme morning types. 19 , 20 …”
Section: Discussionmentioning
confidence: 99%
“…Отримані в групі контролю результати дослідження, знаходять підтвердження в інших подібних роботах. Так, нещодавно, вітчизняними науковцями було продемонстровано, що в здорових людей експресія мРНК per 1 у букальному епітелії була вищою вранці, в той час як bmal1 була більш вираженою у вечірній час незалежно від хронотипу, віку та статі [26]. Аналіз додаткових зарубіжних робіт, наводить дані, що у здорових людей експресія мРНК per1 в слизовій оболонці ротової порожнини та шкіри має найвищі показники в першій половині дня, з наступним зниженням впродовж доби (Bjarnason G. A., 2001).…”
Section: результати дослідження та їх обговоренняunclassified